Spatio-temporal characteristics of the Agulhas leakage: a model inter-comparison study - Holton, Lisa E (Department of Oceanography, 2015)
Investigating the variability of the Agulhas leakage, the volume transport of water from the Indian Ocean to the South Atlantic Ocean, is highly relevant due to its potential contribution to the Atlantic Meridional Overturning Circulation (AMOC) and the global circulation of heat, salt and freshwater, hence to the global climate. As observations of the leakage are scattered in time and space, ocean model outputs are unavoidable to describe its mechanisms of variability. However, the Agulhas leakage is part of a system that still represents a challenge to modellers, because of its degree of non-linearity. As a consequence, this thesis reports the study of the mechanisms of variability of the Agulhas leakage in six ocean model outputs of varying resolution, vertical discretization and boundary conditions. Inter-comparing several model outputs allow one to identify which characteristics of variability are robust. It also provides valuable information on the model speci_cs required to correctly represent the mechanisms of variability of the Agulhas leakage and hence its contribution to climate variability. The Agulhas leakage is estimated at the Good Hope line, a section through the centre of the Cape Basin, using a Eulerian threshold integration method based on the thermo- haline properties of water masses along the line. The threshold method also takes into account the thermohaline biases of each model. Other methods have been tested but the former was selected because it yields an Agulhas Leakage that represents 60% of the actual magnitude as determined by a passive tracer method (only available in one simulation) and captures nearly all of the temporal variability.